Synthesis, characterization, mass spectral fragmentation, thermal study and biological evaluation of new Schiff base ligand and its metal(II) complexes derived from 4-(diethylamino)salicylaldehyde and thiazole moiety - Yernale, Nagesh Gunvanthrao; Udayagiri, Mahadev Dhanraj; Mruthyunjayaswam, Bennikallu Hire Mathada (European Journal of Chemistry, 2016)
A new Schiff base ligand, 2-(4-(diethylamino)-2-hydroxybenzylidene)-N-(4-phenylthiazol-2-yl) hydrazinecarboxamide (L) and its copper(II), cobalt(II), nickel(II) and zinc(II) complexes were prepared and characterized by analytical and spectroscopic methods. The analytical data suggests the composition of the metal complexes to be 1:2 of the type [ML2] for copper(II), cobalt(II) and nickel(II) complexes and 1:1 stoichiometry of the type [MLCl] for zinc(II) complex, where L is the deprotonated Schiff base ligand. The conductance measurement data indicates that all the metal complexes are non-electrolytes. The antioxidant activity of all the compounds was evaluated using the DPPH assay. The Schiff base ligand (L) and its copper(II), cobalt(II) complexes are found to be good antioxidants. The antibacterial and antifungal activity was performed by agar diffusion methods. All the metal(II) complexes inhibited the growth of bacteria and fungi. Also, brine shrimp bioassay was also carried out to study the in vitro cytotoxic properties, the copper(II) and zinc(II) complexes showed good cytotoxic property.